Efektivitas Motion graphic sebagai Media Kampanye Sosial untuk Meningkatkan Kesadaran Literasi Digital generasi muda - Gobel, Citra Yustitya; Zahrannisa, Adea; Muhammad Isla (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The development of digital technology has driven substantial transformation in communication patterns and access to information, especially among the younger generation. However, the relatively low level of digital literacy is still a problem that requires strategic handling. This study aims to examine the effectiveness of using motion graphics a social campaign medium in increasing awareness of digital literacy among the younger generation. research methodology applied uses a quantitative approach, utilizing interview, analysis, and survey techniques. Research respondents were exposed to the campaign through motion graphic media, and their level of understanding was measured through a comparative evaluation between conditions before and after the intervention. results the study show that the use of motion graphics as a social campaign medium significantly increases the understanding and awareness of the younger generation towards digital literacy. Attractive visualization factors, concise message delivery, and a combination of audio and animation elements have been shown to strengthen the appeal and effectiveness of the campaign. These findings indicate motion graphics can be an effective communication strategy in conveying social messages, especially in digital literacy issues. Therefore, motion graphic based social campaigns can be optimized as educational tools for the younger generation in facing challenges digital era.